Characterisation of hydrogen trapping in steel by atom probe tomography - Chen, Y (2017)
Hydrogen embrittlement (HE), which results in an unpredictable failure of metals, has been a major limitation in the design of critical components for a wide range of engineering applications, given the near-ubiquitous presence of hydrogen in their service environments. However, the exact mechanisms that underpin HE failure remain poorly understood. It is known that hydrogen, when free to diffuse in these materials, can tend to concentrate at a crack tip front. In turn, this facilitates crack propagation. Hence one of the proposed strategies for mitigating HE is to limit the content of freely diffusing hydrogen within the metal atomic lattice via the introduction of microstructural hydrogen traps. Further, it is empirically known that the introduction of finely-dispersed distribution of nano-sized carbide hydrogen traps in ferritic steel matrix can improve resilience to HE. This resilience has been attributed to the effective hydrogen trapping of the carbides. However, conclusive atomic-scale experimental evidence is still lacking as to the manner by which these features can impede the movement of the hydrogen. This lack of insight limits the further progress for the optimisation of the microstructural design of this type of HE-resistant steel. In order to further understand the hydrogen trapping phenomenon of the nano-sized carbide in steel, an appropriate characterisation method is required. Atom probe tomography (APT) has been known for its powerful combination of high 3D spatial and chemical resolution for the analysis of very fine precipitates. Furthermore, previous studies have shown that the application of isotopic hydrogen (2H) loading techniques, combined with APT, facilitates the hydrogen signal associated to fine carbides to be unambiguously identified. However, the considerable experimental requirements as utilised by these previous studies, particularly the instrumental capability necessary for retention of the trapped hydrogen in the needle-shaped APT specimen, limits the study being reproduced or extended. In this APT study, a model ferritic steel with finely dispersed V-Mo-Nb carbides of 10-20 nm is investigated. Initially, existing specialised instrumentation formed the basis of a cryogenic specimen chain under vacuum, so as to retain loaded hydrogen after an electrolytic charging treatment for APT analysis. This work confirms the importance of cryogenic treatment for the retention of trapped hydrogen in APT specimen. The quality of the obtained experimental data allows a quantitative analysis on the hydrogen trapping mechanism. Thus, it is conclusively determined that interior of the carbides studied in this steel acts as the hydrogen trapping site as opposed to the carbide/matrix interface as commonly expected. This result supports the theoretical investigations proposing that the hydrogen trapping within the carbide interior is enabled by a network of carbon vacancies. Based on the established importance of the specimen cold chain in these APT experiments, this work then successfully develops a simplified approach to cryo-transfer which requires no instrumental modification. In this approach there is no requirement for the charged specimen to be transferred under vacuum conditions. The issue of environmental-induced ice contamination on the cryogenic sample surface in air transfer is resolved by its sublimation in APT vacuum chamber. Furthermore, the temperature of the transferred sample is able to be determined independently by both monitoring changes to vacuum pressure in the buffer chamber and also the thermal response of the APT sample stage in the analysis chamber. This simplified approach has the potential to open up a range of hydrogen trapping studies to any commercial atom probe instrument. Finally, as an example of the use of this simplified cryo-transfer technique, targeted studies for determining the source of hydrogen adsorption during electropolishing and electrolytic loading process are demonstrated. This research provides a critical verification of hydrogen trapping mechanism of fine carbides as well as an achievable experimental protocol for the observation of the trapping of individual hydrogen atoms in alloy microstructures. The methods developed here have the potential to underpin a wide range of possible experiments which address the HE problem, particularly for the design of new mitigation strategies to prevent this critical issue.